Strategi Pengelolaan Kelas yang Efektif dalam Meningkatkan Disiplin Belajar Siswa - Anwar, Ach. Syafiul; Munirul Abidin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education data according to sources from Databoks states that the Indonesian population with a high school education of 15 years or more reaches 30.22%, while junior high school reaches 22.74%, and elementary school reaches 24.62%. It is very unfortunate that with a very large population, the majority of Indonesians have very little education. Of 12 countries in Asia, Indonesia's education quality is in 12th place, with Vietnam at the bottom, according to a survey conducted by the Political and Economic Risk Consultant (PERC). Data collected by the Swedish World Economic Forum in 2000 showed that Indonesia only ranked 37th out of 57 countries surveyed. In addition, an education quality survey conducted by the same organization in Indonesia shows that Indonesia is only considered a follower rather than a technology leader in 53 countries in the world. This research uses a qualitative descriptive research method by emphasizing literature study or literature study in analyzing variables that are relevant to the discussion in the research. The results of this research show that the low quality of education in Indonesia is caused by the learning process, especially in classroom management. Basically, classroom management is very important so that students can understand learning comfortably because of supportive classroom conditions. There are several strategies obtained in this research, namely planning and implementing class rules, using inclusive teaching techniques and approaches, and developing positive relationships and emotional support for students.